KEBENARAN BERAGAMA DAN KEBEBASAN BERAGAMA - Edi setiawan Edi setiawan; Iskandar Mandika Sebayang; Sahdin Hsb (Madrasa : Jurnal Ilmu Pendidikan dan Teknologi, 2026)
This article examines the dialectic between religious truth and religious freedom in the context of religious pluralism in Indonesia and globally. Using a theological-philosophical approach, this study analyzes three main paradigms in understanding religious truth: exclusivism, inclusivism, and pluralism.The study finds that the tension between *truth claim* and tolerance can be bridged through a deep understanding of transcendental truth that surpasses human formulations. In the Indonesian context, Pancasila provides a unique framework that allows the coexistence of "truth claim" with religious freedom, although there are still implementation challenges in the field